Determinants of HIV serostatus disclosure and assessment of the competence of health care personnel in HIV serostatus disclosure - Adekunle MO; Olutekunbi OA; Animasahun BA; Afadapa MA; Ubuane PO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Background: Disclosure of HIV serostatus is essential for the care and eradication of HIV infection. The World Health Organization recommends disclosure to school-age children and younger children but this practice is commonly hindered by stigmatization and other presumed psychosocial effects of the disease. Objective: To identify limitations to the disclosure of serostatus in HIV-infected children, outcomes of disclosure as well as compare the outcomes of disclosure by either parents/caregiver only with the involvement of health care personnel. Methods: A questionnaire-based study of primary caregivers of children aged 6 years to 18 years with HIV infection who were enrolled at two government-owned tertiary institutions in Lagos State, Nigeria.The healthcare personnel directly involved in the care of these children also participated in the study. Results: A total of 190 primary caregivers participated in the study. In all, 29 health care personnel completely filled the questionnaires. Disclosure (partial and full) was recorded among 31.0%. Older children and children with single parents were more likely to know their HIV status. Similar positive and negative impacts of disclosure were observed irrespective of the individuals involved in the processes. In all, 62.1% of healthcare personnel have had training on disclosure. Conclusion: Disclosure rate in HIV-infected children was low. There is a need for more training of health personnel andeducation of caregivers on the benefits of disclosure as well as theintroduction of effective measures to tacklethe barriers to disclosure.